Northern Lights on the Dead Sea Scrolls : Proceedings of the Nordic Qumran Network 2003-2006 - Petersen, Anders Klostergaard (Studies on the texts of the desert of Judah ;, 2009)
This book originates from a series of conferences held by the Nordic Qumran Network, established 2003. The volume includes some of the best contributions presented at the four symposia held in Helsinki 2003, Oslo 2004, Jerusalem 2005, and Copenhagen 2006.